2022
DOI: 10.1101/2022.05.24.493306
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell walls are dynamically O-acetylated in the green seaweed, Ulva compressa

Abstract: We report that cell wall polymers in the chlorophyte algae may be modified by O-acetylation. The importance of cell wall modifications in the green algae is not well understood, although similar modifications play key roles in land plants by modulating the properties of cell wall carbohydrate polymers. Using a combination of biophysical (Fourier-transform infrared and cross-polarisation heteronuclear correlation nuclear magnetic resonance spectroscopy), biochemical (thin-layer chromatography) and molecular ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Detailed comparative reviews of the complex sulfated polysaccharides found in other ulvophyte groups, including the Ulotrichales, the giant multinucleate (coenocytic) cells of the siphonous Bryopsidales and Dasycladales, and siphonocladous freshwater Cladophorales, are provided elsewhere ( Fernández et al 2015 ; Arata et al 2017 ; Ciancia et al 2020 ). Recently, pectins have been identified in Ulva ( Holzinger et al 2015 ), and the first identification of O-acetylation of pectin in green algae has been described in Bothwell et al 2022 . These results demonstrate that many CW polymers arose in green algae well before the emergence of land plants.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed comparative reviews of the complex sulfated polysaccharides found in other ulvophyte groups, including the Ulotrichales, the giant multinucleate (coenocytic) cells of the siphonous Bryopsidales and Dasycladales, and siphonocladous freshwater Cladophorales, are provided elsewhere ( Fernández et al 2015 ; Arata et al 2017 ; Ciancia et al 2020 ). Recently, pectins have been identified in Ulva ( Holzinger et al 2015 ), and the first identification of O-acetylation of pectin in green algae has been described in Bothwell et al 2022 . These results demonstrate that many CW polymers arose in green algae well before the emergence of land plants.…”
Section: Introductionmentioning
confidence: 99%